Evaluación agronómica y fitosanitaria de 12 líneas y siete variedades de arroz (Oryza sativa L.) en condición de secano en el cantón Mocache. - Bunay Bonilla, Julio Cesar (2013)
This research work was carried out during the rainy season of 2011, at the experimental farm of La María UTEQ, located at Km 7 via Quevedo - The Junction, Quevedo Canton, Los Ríos province. The overall objective was: To evaluate the agronomic performance, healthy and productive lines and 7 of 12 rice varieties sown in rainfed condition Mocache canton, province of Los Rios. and specific objectives were to determine the agronomic performance of 12 lines and 7 rice varieties in rainfed condition Mocache Canton plant and establish the behavior of 12 lines and 7 varieties of rice grown in rainfed condition in the canton Mocache to future research. Twelve lines were evaluated and seven varieties of rice: CC-05-3 P, CC-05-10 P, CC-05-22 P, CC-05-26 P, CC-05-27 P-3 M DORADO, Camula M-2, CC-O3-2 M, 04-1 CC-M, CC-M 04-2, 05-1 CC-M, INIAP-16-1 M, INIAP-4 M and CC-03 varieties , CC-05, INIAP-14, INIAP-16, F-50, Caluma, CC-04, the INIAP-14 is the use as a benchmark for being the largest acreage in the area but also the INIAP 16. We used an experimental design called randomized complete block (BCA), with twelve treatments and three replications. Plots were composed of five rows of five meters, the useful area consisted of the three plants by leaving the remaining border effects. To evaluate the varieties considered the following characters: days to flowering, plant height at harvest, number of tillers and panicles per m2, panicle length, grains per panicle, grains stained vain and panicle, 1000 grain weight and Leaf damage by insects and diseases, yield (kg ha-1), and acames. The varieties and lines in the variables grains per panicle, grains stained grains showed vain and genetic stability. Line CC-03-2M had the highest vegetative growth, making the material more in plant height 104.1 cm research, as the greater number of tillers per plant reached the CC-04-2M with 341, 3 tillers, while the line CC-03-2M reached 5.7 panicles per plant over control (INIAP-14) 178.3 panicles; the same as presented panicles 1.2 cm higher than the control (24.5 cm). The higher number of grains per panicle was recorded in the variety Caluma surpassing the control (93.1 grains) at 37.3 grains, while the variety F-50 had the lowest percentage of empty grains and grains stained with 4.2 % and 0.9%. In days to flowering line CC-05-27P flowered 7.3 days before the witness INIAP-14 (78.3 days), making it more in line early trial, and variety in F-50 1000 seed weight gained more weight with 36.3 grams, while the variety performance CC-05 was higher overtaking control variety with 7061.4 kg / Ha. In the first evaluation of blast percentage was observed lower incidence and severity in varieties INIAP 14 (control), INIAP-16 and line-INIAP 16-1 M with a 0.0% incidence and severity, the second assessment materials lower incidence and severity was observed in the INIAP-14 (2.8%), the INIAP 16 and DC-05 with 5.6% being higher than the control in a new and third assessment blast, the lowest percentage of incidence and severity was shown in the INIAP-14 (control) as the INIAP-16 with 16.6% incidence, and severity index of 0.3 to 0.4% which demonstrates that good characteristics are in relation to the health compared to the F-50 variety which obtained (28.6%) and a severity index to 0.6%, then in a fourth evaluation at 95 days ( after planting) is ratified pointing acceptable averages reaching 25% incidence and 0.8 to 0.9% of severity. Varieties and lines were less affected by insect damage are: CC-04-16 INIAP, INIAP-14 (control), INIAP-16-4 M, 16-1 INIAP-M, CC-05-1 M, CC-04-2 F, CC-04-1 M, CC-05-27 P CC P-05-26 and CC-05-10 P with an average of 1.0% (by showing that the> 1 to 20 % are infected plants which means it is a minor injury), compared to lodging of plants varieties CC-04, Caluma, F-50, CC-05, CC-03 and NIAP-lines 16-1 M, CC-04-2 M-3 M DORADO, CC-05-26 P were resistant to lodging and witness INIAP-14 gained 0.3%. From lodging. Which shows an average acceptable in research. Encourage recommended planting high yielding varieties like (CC-05) since this variable is directly related to the production, also make a dissemination of the results obtained to the medium and small rice farmers to improve their income.